Classifying social media comments using neural networks: Classifying social media comments using neural networks - Ro‘ziboyev, Boburbek (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
Annotation. In the digital age, social media platforms have become pivotal arenas for communication and expression. However, with the vast amount of user-generated content, moderating and understanding the sentiment of social media comments has become increasingly challenging. This thesis explores the application of neural networks in classifying social media comments, aiming to enhance content moderation and sentiment analysis processes. Through the utilization of deep learning techniques, particularly neural networks, this research investigates the effectiveness of various architectures in accurately categorizing social media comments into